General destabilizing effects of eutrophication on grassland productivity at multiple spatial scales - Hautier, Yann; Zhang, Pengfei; Loreau, Michel; Wilcox, Kevin R.; Seabloom, Eric William; Borer, Elizabeth T.; Byrnes, Jarrett E.K.; Koerner, Sally E.; Komatsu, Kimberly J.; Lefcheck, Jonathan S.; Hector, Andy; Adler, Peter B.; et al. (Springer Nature, 2021)
Eutrophication is a widespread environmental change that usually reduces the stabilizing effect of plant diversity on productivity in local communities. Whether this effect is scale dependent remains to be elucidated. Here, we determine the relationship between plant diversity and temporal stability of productivity for 243 plant communities from 42 grasslands across the globe and quantify the effect of chronic fertilization on these relationships. Unfertilized local communities with more plant species exhibit greater asynchronous dynamics among species in response to natural environmental fluctuations, resulting in greater local stability (alpha stability). Moreover, neighborhood communities that have greater spatial variation in plant species composition within sites (higher beta diversity) have greater spatial asynchrony of productivity among communities, resulting in greater stability at the larger scale (gamma stability). Importantly, fertilization consistently weakens the contribution of plant diversity to both of these stabilizing mechanisms, thus diminishing the positive effect of biodiversity on stability at differing spatial scales. Our findings suggest that preserving grassland functional stability requires conservation of plant diversity within and among ecological communities.